2009
DOI: 10.1021/jp8069496
|View full text |Cite
|
Sign up to set email alerts
|

Liposome−Prilocaine Interaction Mapping Evaluated through STD NMR and Molecular Dynamics Simulations

Abstract: We have examined the interaction of the neutral and protonated species of the local anesthetic prilocaine (PLC) with phosphatidylcholine (PC) bilayers combining experimental ((1)H NMR) and theoretical (molecular dynamics simulations) approaches. DOSY experiments allowed the determination of the association constants of protonated (Ka = 9 L/mol) and neutral (Ka = 21 L/mol) PLC to egg PC liposomes. Saturation transfer difference (STD) experiments showed a different trend depending on pH: At high pH the PLC hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 35 publications
6
21
0
Order By: Relevance
“…Investigating the topologies of PLC in β‐CD in EPC liposomes at different pHs by NMR required full characterization of simple binary mixtures in aqueous solutions of PLC, β‐CD and EPC. The pH influence on PLC/EPC complex topology was fully assessed by applying STD, and molecular dynamics simulations, revealing that at pH 10 the PLC molecules were mostly imbedded into the liposome, whereas at pH 5.5, the PLC behavior was modulated by the dynamic equilibrium between the charged (in the aqueous phase) and uncharged species (in the liposome)26 (Fig. 1).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Investigating the topologies of PLC in β‐CD in EPC liposomes at different pHs by NMR required full characterization of simple binary mixtures in aqueous solutions of PLC, β‐CD and EPC. The pH influence on PLC/EPC complex topology was fully assessed by applying STD, and molecular dynamics simulations, revealing that at pH 10 the PLC molecules were mostly imbedded into the liposome, whereas at pH 5.5, the PLC behavior was modulated by the dynamic equilibrium between the charged (in the aqueous phase) and uncharged species (in the liposome)26 (Fig. 1).…”
Section: Resultsmentioning
confidence: 92%
“…3) indicated an interaction between PLC and the liposome vesicles, causing saturation transference from the liposomes to all PLC hydrogens and indicating that PLC is imbedded into the liposome vesicles. The EPC saturation transfer was more efficient for the PLC aromatic moiety (100%) which might indicate a longer residence time in the liposome vesicles, consistent with previously published results using PLC‐EPC 26…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results pointed towards the fact that improved solubility in biological media could be achieved by choosing a six-atom side chain length and that enhancement of membrane interactions/penetration could be achieved by hydroxyl substitutions on the C6 lateral chain. Cabeça et al [108] applied molecular dynamics (MD) simulations and NMR spectroscopy to examine the interaction of the neutral and protonated species of the local anaesthetic prilocaine (PLC) with phosphatidylcholine (PC) bilayers. The diffusion-ordered 2D NMR spectroscopy (DOSY) experiments showed that neutral PLC has a higher affinity for the liposome environment.…”
Section: Ligand-dna Ligand-rna and Ligand Membrane Interactionsmentioning
confidence: 99%
“…From a theoretical perspective, atomistic molecular dynamics (MD) computer simulations are being successfully applied to investigate the effects of various LAs on model phospholipidic membranes at a molecular level18–23. However, because of the wide variety of these compounds, it is often needed to develop new interaction potential parameters that allow the study of these systems by MD simulations.…”
Section: Introductionmentioning
confidence: 99%